The effect of smoking, obesity and diabetes on recurrence‐free and overall survival in patients with stage III colon cancer receiving adjuvant chemotherapy. Issue 3 (7th February 2021) - Croese, Alex; Gartrell, Richard; Hiscock, Richard; Lee, Margaret; Gibbs, Peter; Faragher, Ian; Yeung, Justin
Abstract: Background: The association between smoking, diabetes and obesity and oncological outcomes in patients with stage III colon cancer treated with surgery and adjuvant chemotherapy is unclear. Aim: To evaluate whether smoking, obesity and diabetes are associated with the disease‐free survival and overall survival rates of patients with stage III colon cancer who have received adjuvant chemotherapy. Methods: Patients were selected from the prospectively maintained Australian Cancer Outcomes and Research Database (ACCORD). All stage III colon cancer patients who received adjuvant chemotherapy between January 2003 to December 2015 were retrospectively analyzed. The three primary exposures of interest were smoking status, body mass index (BMI) and diabetic (DM) status. The primary outcomes of interest were disease‐free survival (DFS) and overall survival (OS). Results: A total of 785 patients between 2003 and 2015 were included for analysis. Using Kaplan‐Meier survivorship curves, there was no association between OS and smoking ( P = .71), BMI ( P = .3) or DM ( P = .72). Similarly, DFS did not reveal an association with smoking ( P = .34), BMI ( P = .2) and DM ( P = .34). Controlling for other covariates the results did not reach statistical significance in adjusted multiple regression models. Conclusion: Smoking, obesity and DM were not shown to influence DFS or OS for patients with stage III colon cancer who have received adjuvant chemotherapy.